MENGHITUNG SPESIFIC ENERGY CONSUMPTION CALCINING ZONE ROTARY KILN PT. SEMEN BATURAJA (PERSERO) TBK. - Panjaitan, Roma Tua; Anugrah, Rendotian; Safaruddin, Safaruddin (Jurnal Multidisipliner Bharasumba, 2022)
One of the equipment in the factory that uses a lot of energy is a rotary kiln. Rotary Kiln is a cement product mixture (clinker) burner which is used to raise materials to hig temperatures 9calcination) in a continous process. it can be analyzed that the more coal and the higher the net heating value of the coal supplied for combustion in the rotary kiln burner, the higher the specific energy consumption value because the heat of flue gas from burning coal entering the calcining zone of the rotary kiln will be even greater.From the calculations that have been done, it can be evaluated that the specific energy consumption of rotary kiln calcining zone is influenced by several factors, including; the amount of feed that enters the calcining zone, the amount of fuel (coal) used, the temperature of the kiln outlet gas, air and steam leaks in the kiln wall including heat loss that occurs in the kiln. (Adam Atmaca, 2014). The specific energy consumption calcining zone of the rotary kiln after the calculation can be categorized as good for the size of the heating room which has the most heat loss possibilities. However, the specific energy consumption of the rotary kiln calcining zone can still be maximized by improvising the components of the equipment, based on the relatively large percentage of heat loss, it can be done by controlling the coal feed, excess O2 according to the needs of the mass entering the kiln to be heated so as to minimize heat loss. in the calcining zone of the rotary kiln.